2014
DOI: 10.14319/ijcto.0201.9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical dosimetric impact of Acuros XB and analytical anisotropic algorithm (AAA) on real lung cancer treatment plans : review

Abstract: Photon dose calculation algorithms in treatment planning system could affect the accuracy of dose delivery when tissue heterogeneity is involved along the beam path. Treatment planning for lung cancer is challenging, especially in the case of treatment plan involving small fields. The combination of low-density (air) medium and small fields cause charge particle disequilibrium nears the air/tissue interface. Beam modeling within the dose calculation algorithms must also employ an accurate method of accounting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 36 publications
(83 reference statements)
1
24
1
Order By: Relevance
“…Dose differences may also vary depending on the photon beam energy used for calculations. [13,14,15] The results of this study, however, showed no clear dependency on the field size. Similarly, difference between the PBC and measurements did not show a clear trend when results at various points (P1, P2, P3, and P4) were compared with each other.…”
Section: Discussioncontrasting
confidence: 73%
“…Dose differences may also vary depending on the photon beam energy used for calculations. [13,14,15] The results of this study, however, showed no clear dependency on the field size. Similarly, difference between the PBC and measurements did not show a clear trend when results at various points (P1, P2, P3, and P4) were compared with each other.…”
Section: Discussioncontrasting
confidence: 73%
“…The AAA algorithm used in this study was proved to be better than the pencil beam convolution algorithm 18. However, it was expected that the calculation accuracy would further be improved if the Acuros XB algorithm19 was used.…”
Section: Discussionmentioning
confidence: 85%
“…We have used analytic anisotropic algorithm (AAA) for dose calculations, which is a RTOG‐acceptable algorithm for dose computations for RTOG lung protocols. Several papers have pointed out the limitation of AAA in the presence of low‐density heterogeneity (21‐25) . Recently, a number of investigators have recommended the use of Acuros XB, a new dose calculation algorithm available in Eclipse, for dose calculations in lung treatment plans (21‐25) .…”
Section: Discussionmentioning
confidence: 99%